Process method for synthesizing methanol through carbon dioxide hydrogenation - QIU DONG; HE JIAN; DONG TIANLEI; YIN HUIQIN; TIAN XIANGUO; YU YANG; CHEN HAIBO; WANG QIONG; TAN JIEDONG; XIE TIANMING (2016)
The present invention belongs to the technical field of synthesis of methanol from carbon dioxide, and relates to a process method for synthesizing methanol through carbon dioxide hydrogenation. According to the main process, CO2 reverse water gas shift, methanol synthesis reaction and gas re-circulation process are used, wherein the shift reaction and the synthesis reaction are performed in the upper half section and the lower half section inside the same coupling reactor, the reaction temperature in shift reaction at the upper half section is 220-320 DEG C, the synthesis reaction at the lower half section is conducted at the low temperature of 210-280 DEG C in the presence of a traditional methanol synthesis catalyst, the system operating pressure is 3.0-9.0 Mpa, and the space velocity is 4000-20000 h<-1>. According to the present invention, during the reaction process, the process is simple, the operating conditions are mild, the technology is mature and reliable, the total carbon conversion rate is high,